Analysis of teachers’ technological competencies and their performance at a higher education level - Hafeez, Muhammad; Naz, Vajiha; Tahira, Fatima (LPMPP Universitas Negeri Yogyakarta, 2025)
Technology has become the main game changer in all the fields of study, including education. The main purpose of this research was to analyze the teachers’ technological competencies and their performance at the higher education level. The teachers’ technological competencies were analyzed in six elements of technology, including perceptions, technological knowledge, perceived ease of use, perceived usefulness, and skills in using technology. The teachers’ performance in using technology in the teaching and learning process was also determined. The study consisted of two samples: one from the teachers of the six social sciences departments at the six public universities of South Punjab, Pakistan, and the other from the students of the 6th, 7th, and 8th semesters of the six social sciences departments at the six public universities of South Punjab, Pakistan. The sample size consisted of 497 teachers and 611 students. The samples were selected by using a stratified random sampling technique. Two questionnaires, one for teachers and the other for students, were adopted from the literature to collect the data. SPSS-25 was used to analyze the collected data. Frequency distribution, descriptive statistics, and correlation analysis were done to analyze the data and to interpret the results. The findings of the study indicated that most of the teachers of the social sciences departments at the public universities of South Punjab, Pakistan, had a lack of technological competencies, and their performance was also not good. The results also indicated a high positive correlation between teachers’ technological competencies and their performance at the higher education level. Some serious steps are required to improve the teachers’ technological competencies and performance at the higher education level.